Dental Caries in Permanent First Molar and Its Association with Carious Primary Second Molar among 6-11-Year-Old School Children in Sunsari, Nepal - Santosh Kumari Agrawal; Tarakant Bhagat; Ashish Shrestha (Hindawi Limited, 2023)
The permanent first molar (PFM) plays an essential role in maintaining the dental and overall health of an individual. It is the most susceptible tooth to dental caries due to its early eruption and location near the primary second molar in the oral cavity. We assessed the clinical status of the PFM and its association with carious primary second molars among 6-11-year-old children in Sunsari, Nepal, from January 2019 to December 2021. We recorded DMFT/DMFS and dft/dfs indices of the first permanent molar and secondary primary molar. Chi-square, logistic regression, and Spearman rank correlation (rs) were used to explore the association between carious molar lesions. Of the 655 children, only 612 had all first permanent molars. The prevalence of caries was higher in the second primary molar (70.9%) than in the PFM (38.6%). In both molars, the occlusal surface was the most commonly affected surface by dental caries. A significant association (p<0.01) was found between the decayed primary second molar and the decayed PFM. A moderate but statistically significant correlation (p<0.01) was found between the occurrence of dental caries in both the molars.